Effective dielectric loss (tan δ) reduction of CaCu3Ti4O12 (CCTO) via various addition of glasses - Ab Rahman, Mohd Fariz; Ain, Mohd Fadzil; Mohamed, Julie Juliewatty; Ahmad, Zainal Arifin (The American Ceramic Society, 2018)
Addition of various glasses has successfully reduced tan δ of CCTO‐based ceramics. Less amounts (0‐1.0 wt%) of glasses (BaO‐SrO‐Nb2O5‐B2O3‐SiO2 [BSNBS] and SrO‐B2O3‐SiO2 [SBS], respectively) were added into pure CCTO and sintered at 1040°C for 10 hours. The phase formation and microstructure of each sample were characterized using X‐ray diffraction and scanning electron microscopy, respectively. The dielectric behavior of the samples was measured at 1 MHz. The addition of BSNBS and SBS glasses (≤0.5 wt%) successfully reduced tan δ of CCTO from 0.5 until 0.4 and 0.39, respectively, and simultaneously increased εr. Smaller tan δ and ɛr were further obtained when the added glasses were more than 0.5 wt%. These behaviors were due to segregation of glasses together with precipitation of CuO which decreased the grain size, and caused the presence of pores at grain boundaries. Therefore, small amount of various additions of glasses could modify the CCTO dielectric properties.